Synthesis of hydrophobic photoluminescent carbon nanodots by using L-tyrosine and citric acid through a thermal oxidation route - Gude, Venkatesh (Beilstein Journal of Nanotechnology, 2014)
Hydrophobic photoluminescent carbon nanodots (CNDs) were fabricated by using citric acid and L-tyrosine precursor molecules through a simple, facile thermal oxidation process in air. These CNDs (less than 4 nm in size) exhibited a characteristic excitation wavelength dependent emission and upconversion emission properties and are insoluble in water, but soluble in organic solvents. FTIR and 1H NMR analyses showed a selective participation of L-tyrosine molecule during the carbonization process at 220 °C without a disturbance of its benzylic protons and aromatic phenyl ring bearing hydroxy group. TEM and XRD studies revealed a quasi-spherical morphology and poor-crystalline nature of CNDs. Because the presence of the hydroxy group of L-tyrosine is dominating at the surface, these CNDs are also soluble in water under basic conditions. The effects of base and silver nanoparticles on the luminescence properties of CNDs were studied and a quenching of fluorescence was observed. These tyrosine-passivated CNDs are applicable for both biologically and commercially.
Keywords: composite materials; fluorescence quenching; hydrophobic; luminescence; upconversion